Comparative study of continuous lateral osteotomy and microperforating osteotomy in patients undergoing primary rhinoplasty - Pizzamiglio, Diego Sherlon; Berger, Cezar Augusto Sarraf (International Archives of Otorhinolaryngology, 2012)
Introduction: Lateral osteotomies play an important role in rhinoplasty and can be performed with different techniques.Objective: To compare the results of narrowing of the nasal dorsum and base through 2 types of lateral osteotomy: continuous and microperforating.Method: We selected 74 patients undergoing rhinoplasty: 37 patients underwent lateral continuous osteotomy and the other 37 underwent microperforating osteotomy, all performed by the same surgeon. We analyzed frontal photography from the pre- and post-operative (6 months) periods, evaluating the width of the nasal dorsum and base. This was a retrospective study.Results and Conclusion: Using Student's t-test, statistical analysis concluded that there was a statistically significant difference in the post-operative narrowing of the nasal dorsum and base following both osteotomy techniques, and there was no statistically significant difference between the 2 techniques.
Keywords: rhinoplasty; osteotomy; photography